Choriocarcinoma masculine singular case - clinicopathologic about four cases of choriocarcinoma in the Hospital Obrero de Lima considerations - De Pareja Bracamonte, Vilma (2015)
Choriocarcinoma or chorioepithelioma is a malignant tumor, whimsical clinical evolution, developed in the epithelial cells lining the chorionic villi whose histological and functional properties endocrine played. In exceptional cases, choriocarcinoma cell originates dysembryoplastic germs, ie a teratoma that usually is testis or ovary.